Modern data on embryogenesis and functional morphology of thymus (Literature review, part I) - L. Kupriianova; S. Ivanchenko (Kazimierz Wielki University, 2021)
In the following article we have provided modern data on main stages of implementation, formation as well as stabilization of functional activity of thymus of the fetus on different stages of fetal development. Thus, we have analyzed specific features of gland's location in case of children, adolescents and adults. We have described two main stages of the organ's ontogenesis. In addition, histological features of the fetal thymus implemetation, starting with the 8th week of embryonic development were studied and provided below. The criteria of completion of the gland's formation on the gestational term of 24 weeks were clearly emphasized. The stages of maturing of lymphocytes as well as appearance of the surface markers of the lymphocytes on them as well as division of the T-cells into subpopulations were described. The role of thymus in the sphere of formation of all types of the organism's immune defence was explained. We have analyzed an endocrine function of the gland with providing the hormones, hormone-like substances, as well as extracts of the organ, which have their influence onto lymphoid tissue development  as well as play their leading role in the hormonal homeostasis of the child's organism. The morphological features of the main structural components of the gland, as well as their functions in the thymus stabilization were disclosed. The nature of relations between structural components was clearly described. It has been proved also, that in case of full-term fetus, the thymus is a main lymphoid organ, which is structurally and functionally formed for the moment of birth. Moreover, under the conditions of the physiological pregnancy the lymphoid and epithelial components are sufficiently and harmoniously developed, and the thymocytes are differentiated and immunologically mature. Finally, we came up with the conclusion, that the pathology of pregnancy and childbirth can lead to the impaired embryogenesis and fetogenesis of the fetal thymus.